Ulcerative colitis model triggers gut α-Synuclein aggregation without brain involvement or neuronal loss in female rats - Espinosa-Oliva, Ana María; Vázquez-Carretero, María Dolores; Ruiz, Rocío; Roca-Ceballos, María A.; García-Miranda, Pablo; Peral, María José; Soto, Manuel Sarmiento; Herrera, Antonio J.; Venero, José Luis; de Pablos, Rocío M. (Frontiers in Immunology, 2026)
IntroductionDespite being the second most common neurodegenerative disorder, the mechanisms underlying the onset and progression of Parkinson’s disease (PD) remain poorly understood, and no curative treatment is currently available. The Braak hypothesis offers an intriguing framework for explaining both the origin and development of the disease, proposing that PD begins in the gut and subsequently spreads to the brain.MethodsIn previous studies, our group developed a novel PD model in which peripheral inflammation, triggered by administering dextran sodium sulphate (DSS) in the drinking water of male Wistar rats, recapitulates key features of PD in both the gut and the brain. This model supports the Braak hypothesis and highlights the relevance of the gut-brain axis. Using the same model, the present study aimed to determine whether sex influences peripheral inflammation and the resulting neuropathology in the substantia nigra (SN) of female Wistar rats.ResultsOur findings show that while DSS treatment induces comparable levels of colonic inflammation and phosphorylated α-synuclein accumulation in both sexes, it does not produce α-synuclein aggregation or dopaminergic neuronal loss in the SN pars compacta of female rats.ConclusionThese results underscore the critical importance of considering sex differences in experimental PD models and in clinical practice, as such differences may significantly influence PD pathogenesis.